Real estate law - Jennings, Marianne (Thomson/South-Western West, 2008)
REAL ESTATE LAW charts new territory with its clear and cutting-edge coverage of the basics and trends in the laws that affect real property. The text will help you really understand and grasp the material while helping you develop your problem-solving skills in your professional and personal real estate transactions. Each chapter reveals how you will use the material.